1997
DOI: 10.1042/bj3270233
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of cAMP-induced Ca2+ influx in Dictyostelium: role of phospholipase A2

Abstract: cAMP-induced Ca2+ influx in Dictyostelium follows two pathways: a G-protein-dependent pathway where influx is reduced by 50-70% in Galpha2 and Gbeta-negative strains and a heterotrimeric G-protein-independent pathway. Using a pharmacological approach, we found that phospholipase A2 (PLA2) is the target of both pathways. The products of PLA2 activity, arachidonic acid (AA) and palmitic acid, induced Ca2+ influx to a similar extent as cAMP. Half-maximal activation occurred at 3 microM AA and saturation at 10 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…This accords with the suggestion that chemoattractants such as cAMP may activate phospholipase A2, resulting in the production of long chain fatty acids and the release of Ca 2ϩ from intracellular stores, depleting them and thereby activating influx (45).…”
supporting
confidence: 68%
See 2 more Smart Citations
“…This accords with the suggestion that chemoattractants such as cAMP may activate phospholipase A2, resulting in the production of long chain fatty acids and the release of Ca 2ϩ from intracellular stores, depleting them and thereby activating influx (45).…”
supporting
confidence: 68%
“…All work was done with Dictyostelium discoideum strain AX2 (2), with the mutant strains derived from it, HG1774 (calreticulin deficient), HG1770 (calnexin deficient), HG1772 (calreticulin and calnexin deficient) (35), and with aequorin-expressing transformants derived from them (HPF401 from AX2, HPF608 from HG1774, and HPF609 and HPF610 from HG1770). For axenic growth the amoebae were incubated as previously in shaken culture (150 rpm) at 23°C in axenic medium (45) or at 21°C in HL5 medium (38).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in Dictyostelium have suggested that products of PLA2 action, such as arachidonic acid, affect chemoattractantinduced Ca 2+ influx and can trigger Ca 2+ influx directly (Schaloske and Malchow, 1997). In mammalian cells, arachidonic acid is involved in the release of Ca 2+ from internal stores by regulating calcium channels (Osterhout and Shuttleworth, 2000;Shuttleworth and Thompson, 1999).…”
Section: Phospholipase A2 and Phospholipase C In Dictyosteliummentioning
confidence: 99%
“…Ca 2+ is not required to activate PLA 2 (Chen et al, 2007), but PLA 2 inhibitors suppress cAMPdependent influx of Ca 2+ and addition of the putative PLA 2 product AA rescues Ca 2+ influx in the presence of PLA 2 inhibitors (Schaloske and Malchow, 1997). Nonetheless, cells genetically deficient for one of the several putative PLA 2 genes in Dictyostelium display normal Ca 2+ influx and addition of AA to pla2-null cells treated with LY2940004 partially rescues the ability of these cells to aggregate (Chen et al, 2007).…”
Section: Pla 2 -Signalingmentioning
confidence: 99%